Valproic acid enhances the paclitaxel activity in respiratory tract cancer cells - Al-Khafaji, Ahmed Salim Kadhim; Alnefaie, Ghaliah; Al-Shammari, Ahmed Majeed (Journal of Contemporary Medical Sciences, 2019)
Objective: Epigenetic therapies have already been introduced into clinical cancer management. The main objective of this study is to explore the potential of modulating paclitaxel efficiency using two epigenetic modifiers; valproic acid and decitabin. Methods: the potential sensitisation of lung and oral cancer cells to paclitaxel was examined by two well-known epigenetic modifiers; the DNA methyltransferase (DNMT) inhibitor Decidabine and histone deacetylase (HDAC) class I inhibitor Valproic acid (VPA). The effect epigenetic modifiers were tested using qPCR and pyrosequencing techniques utilising respiratory tract cancerous tissues and cell lines. Results: The results exhibited that VPA was an effective epigenetic sensitizer for treating lung and head and neck cancerous cells (A549, SKLU1 and BHY). 48 hours prior to paclitaxel addition, a significant increase (p<0.01) of the paclitaxel toxicity was observed when the cancer cells pre-treated with VPA for 48hr and subsequently with paxlitaxel for 72 hours. Interestingly, mRNA expression of AURKA was reduced by VPA treatment. The result also demonstrated that p53 status was involved in VPA- mediated paclitaxel sensitisation of HBEC cell lines to paclitaxel. VPA seems to potentiate p53 wild type cells (HBEC-3KT) to paclitaxel, while p53 HBEC knockouts showed less cytotoxic effect of paclitaxel after exposure to 0.5 mM VPA. On the other hand, decitabin was not efficient to sensitise any of the cell lines to paclitaxel when used in either a synchronous or a preceding manner. In addition, the pyrosequencing analysis of the methylation status of the different gene promoters in the lung tumour and normal tissues showed that all the promoters were unmethylated. Conclusion: It can be concluded that the epigenetic modifier VPA can alter the response of cancer cells to paclitaxel treatment. Further investigation is needed to explore the epigenetic mechanism of sensitising cancerous cells to paclitaxel.